Epigenetic regulation in oogenesis and fetal development: insights into m6A modifications - Liu, Lusheng; Ge, Danxia; Lin, Yumeng; Han, Zhongyu; Zhao, Heng; Cao, Liqin; Wu, Xi; Ma, Guizhi (Frontiers in Immunology, 2025)
The unique physiological structure of women has led to a variety of diseases that have attracted the attention of many people in recent years. Disturbances in the reproductive system microenvironment lead to the progression of various female tumours and pregnancy disorders. Numerous studies have shown that epigenetic modifications crucially influence both oogenesis and foetal development. m6A, a modification at the mRNA level, consists of three parts, namely, writers, erasers, and readers, which are involved in several biological functions, such as the nucleation and stabilisation of mRNAs, thereby regulating the development of reproductive system diseases. In this manuscript, we delineate the constituents of m6A, their biological roles, and advancements in understanding m6A within the maternal–foetal immunological context. In addition, we summarise the mechanism of m6A in gynaecological diseases and provide a new perspective for targeting m6A to delay the progression of reproductive system diseases in clinical practice.